You Should Be the Specialist! Weak Mental Rotation Performance in Aviation Security Screeners – Reduced Performance Level in Aviation Security with No Gender Effect - Krüger, Jenny K.; Suchan, Boris (Frontiers in Psychology, 2016)
Aviation security screeners analyze a large number of X-ray images per day and seem to be experts in mentally rotating diverse kinds of visual objects. A robust gender-effect that men outperform women in the Vandenberg & Kuse mental rotation task has been well documented over the last years. In addition it has been shown that training can positively influence the overall task-performance. Considering this, the aim of the present study was to investigate whether security screeners show better performance in the Mental Rotation Test (MRT) independently of gender. Forty-seven security screeners of both sexes from two German airports were examined with a computer based MRT. Their performance was compared to a large sample of control subjects. The well-known gender-effect favoring men on mental rotation was significant within the control group. However, the security screeners did not show any sex differences suggesting an effect of training and professional performance. Surprisingly this specialized group showed a lower level of overall MRT performance than the control participants. Possible aviation related influences such as secondary effects of work-shift or expertise which can cumulatively cause this result are discussed.